Islamic Philosophy of Education and Our Challenges Ahead (IIUC Studies, 2015)
Philosophical foundation of any area of study or disciple is very important aspect to deal with before undertaking comprehensible plans and programs to implement. Education is a quite undefined and ever expanding area of human resource development directly related to the nation-building, national security, and overall emancipation of the masses. Creaking highly professional and skilled human resources is indeed one of the prime goals for any education system. However, at the ground levels, our failure to disseminate minimum knowledge based on objective assimilation of required information may endanger the survival of the entire nation. Feeding the nation with only greed for money, wealth, and power may cause tremendous damage to the psyche of a nation leading to disastrous consequences for educational policies as well. Finding right kind of balance for educational and cultural system is a very big challenge. This complicated challenge with many ideological, social, and economic dichotomies can only be met by reforming education at its core. Any Morally sound and economically viable system of education needs technical support all the way from top to bottom. Simple mechanical and rote learning of anything may be good for some individual drives to be fulfilled immediately. But those drives as a whole may not be befitting to save a nation from ignorance, moral decadence and arrogance. Thus we can hardly overemphasize the importance of building a comprehensive philosophical foundation based on some universal and Islamic values directed to creating humble souls with cutting edge technological know-how beneficial for the entire ummah, human race, and major causes of environmental protection. The major objective of writing this paper is to articulate some of the challenges we have been confronting in our education system as a whole and to endeavor finding a few approaches to address at least some of those problems to help ourselves in making us better equipped to bring happiness, prosperity, and humility around us all, and also to keep trying to leave the planet a better place for the generations to come for their safety, security, and spiritual salvation in worldly life and hereafter.IIUC Studies Vol.9 December 2012: 59-78